Precision Farming: Exploring the Challenges and Opportunities for Smallholder Farmers in Chile - Fernandez-Campusano, C (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
The objective of this study is to analyse the challenges and opportunities that Precision Farming (PF) offers for agriculture in Chile, highlighting the possibilities it offers for solving agricultural problems as well as the challenges that hinder its application by small- and medium-sized farmers. A qualitative content analysis was conducted on technical government publications and academic publications focused on precision agriculture, which highlighted the elements that hinder the implementation of PF in smaller agricultural systems, i.e., small farmers. The results show that among the main problems that PF can help solve are spring frosts, low product calibre, fruit rot, low sugar content in fruit, and water stress, among others. The solutions that PA could offer, as outlined in the review, are varied and include frost forecasting, crop monitoring, application of inputs, and selection of more drought-tolerant crops, to name a few. On the other hand, another relevant finding is the fact that small farmers face structural difficulties in accessing PF technologies, due to their high cost (technology transfer) but also to the lack of support from state institutions.